Systematic identification of reference genes for qRT-PCR of Ardisia kteniophylla A. DC under different experimental conditions and for anthocyanin-related genes studies - Wang, Wentao; Zhang, Xiaohang; Xu, Xiaoxia; Xu, Xingchou; Fu, Lin; Chen, Hongfeng (Frontiers in Plant Science, 2023)
Ardisia kteniophylla A. DC, widely known as folk medicinal herb and ornamental plant, has been extensively investigated due to its unique leaf color, anti-cancer and other pharmacological activities. The quantitative real-time PCR (qRT-PCR) was an excellent tool for the analysis of gene expression with its high sensitivity and quantitative properties. Normalizing gene expression with stable reference genes was essential for qRT-PCR accuracy. In addition, no studies have yet been performed on the selection, verification and stability of internal reference genes suitable for A. kteniophylla, which has greatly hindered the biomolecular researches of this species. In this study, 29 candidate genes were successfully screened according to stable expression patterns of large-scale RNA seq data that from a variety of tissues and the roots of different growth stages in A. kteniophylla. The candidates were then further determined via qRT-PCR in various experimental samples, including MeJA, ABA, SA, NaCl, CuSO4, AgNO3, MnSO4, CoCl2, drought, low temperature, heat, waterlogging, wounding and oxidative stress. To assess the stability of the candidates, five commonly used strategies were employed: delta-CT, geNorm, BestKeeper, NormFinder, and the comprehensive tool RefFinder. In summary, UBC2 and UBA1 were found to be effective in accurately normalizing target gene expression in A. kteniophella regardless of experimental conditions, while PP2A-2 had the lowest stability. Additionally, to verify the reliability of the recommended reference genes under different colored leaf samples, we examined the expression patterns of six genes associated with anthocyanin synthesis and regulation. Our findings suggested that PAP1 and ANS3 may be involved in leaf color change in A. kteniphella. This study successfully identified the ideal reference gene for qRT-PCR analysis in A. kteniphella, providing a foundation for future research on gene function, particularly in the biosynthesis of anthocyanins.